Pengaruh Potensi Industri Garam, Produksi Garam, dan Luas Lahan Industri Garam terhadap Pertumbuhan Ekonomi di Kabupaten Sampang - Ach Isbir Fikry Syaukany; M.Taufiq (CV. Ulil Albab Corp, 2022)
Salt is one of Indonesia's strategic commodities where its use is not only for human consumption but also as industrial raw material as well as for salting and various foods. In general, salt business in Indonesia is produced by evaporating seawater on a piece of coastal land with the help of wind and sunlight as a source of evaporation energy. Salt production can be carried out by coastal communities without any special skills. This can be a job opportunity for coastal communities. Talking about salt, of course it cannot be separated from an area called Madura which has long been known as